Traumatic Exit, Identity Narratives, and the Ethics of Hospitality. (September 2019) - Appadurai, Arjun
The argument of this essay is that migrants, especially refugees, in the contemporary globalized world are inevitably second-class citizens because their stories do not fit the narrative requirements of modern nation-states. As a result, there is no easy way for them to fit either their memories or their aspirations into acceptable forms that fit the criteria for full citizenship in most states. This essay argues for renewed attention to the relationship between migrants and mediation, especially based on the idea that archives are not only records of the past but are also maps for the future.